Maintaining Marital Stability After Infidelity: A Case Study of Childless Couples from the Perspective of Maqāṣid al-Sharīʿah - Nadhifa Salsabila; Ruston Kumaini (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2026)
Infidelity is one of the most significant marital problems, often leading to conflict and undermining marital harmony. Nevertheless, many couples choose to preserve their marriage despite experiencing betrayal, including those who have not yet had children. This phenomenon is noteworthy because the absence of children would seemingly make separation less complicated; however, many couples still decide to remain together. This study examines the factors underlying this decision and analyzes them through the perspective of Maqāṣid al-Sharīʿah. A qualitative case study design combined with a normative-empirical approach was employed. Data were collected through in-depth interviews with two participants who had experienced spousal infidelity, had no children, and chose to continue their marriages. The findings reveal that the decision to remain married is shaped by multidimensional emotional, social, psychological, and spiritual considerations. The decision also generates ambivalent consequences. While marital harmony and emotional intimacy decline because of unresolved betrayal, interaction and communication may increase as the unfaithful spouse demonstrates remorse and attempts to restore the relationship. From the perspective of Maqāṣid al-Sharīʿah, preserving the marriage is justifiable when it promotes maṣlaḥah by safeguarding progeny (ḥifẓ al-nasl), psychological well-being (ḥifẓ al-nafs), and religion (ḥifẓ al-dīn), and is accompanied by sincere repentance, reconciliation, and genuine efforts to rebuild the marital relationship.